Ajax in America, or Catharsis in the Time of Terrorism. (November 2020) - Roberts, Matthew
Abstract : Originally funded by the US Department of Defense in 2009, Theater of War Productions' first project, Theater of War, performs dramatic readings of Ajax at military bases, hospitals, and academic institutions throughout the United States. Developed by Bryan Doerries, Theater of War brings awareness to the epidemic of suicide and other forms of violence committed by American military service members in the wake of the United States' so-called 'war on terror'. But like Ajax, American military personnel typically turn to violence only after being betrayed by the institutions that they served. This article follows how Ajax 's more modern manifestation disrupts the tragic protagonist's status as a sacrificial victim whose death precipitates tragedy's cathartic effect, and challenges what René Girard calls the 'scapegoat mechanism' and its socio-political function. It argues that Ajax's appearance as a cathartic figure in American society provokes spectators and artists to reckon with the conditions that can cause military personnel to act violently, and inspires protests against broader hegemonic socio-political structures and the military culture that sustains them. Matthew Roberts is Assistant Professor and Librarian for Comparative and World Literature, English, and Drama at the University of Illinois at Urbana-Champaign.